Despatches and correspondence transmitted to the House of Assembly in Governor Douglas' message of 3rd September, 1863 [electronic resource]. - Douglas, James, Sir, 1803-1877.; Vancouver Island (B.C.). Governor (1851-1863 : Douglas) ([Victoria, B.C.? : s.n.], 1863)
Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 17274-17277. Cover title. Electronic reproduction. Mode of access: Internet. 44